2013
DOI: 10.1586/egh.12.61
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological study on the incidence of gastroesophageal reflux disease symptoms in patients in acute treatment with NSAIDs

Abstract: Gastroesophageal reflux disease (GERD) is one of the most common disorders in medical practice. The prevalence of GERD in Spain has been reported to be 15%. GERD is associated with esophageal and extra-esophageal complications and with a negative impact on the patients' related quality of life. Several risk factors have been related with the development of GERD, including smoking, coffee intake, alcohol consumption and use of medication, such as NSAIDs. If untreated, GERD symptoms can lead to a decrease of pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
0
6
0
3
Order By: Relevance
“…In an observational study of French adults, NSAID or aspirin use was a significant risk factor for GERD symptoms [39]. Similar studies from different parts of the globe, including US and UK showed that GERD symptoms were more common in NSAID users than in non-users [40][41][42][43]. However, a recent study from Moscow reported that NSAID use did not affect the prevalence of GERD [44].…”
Section: Discussionmentioning
confidence: 99%
“…In an observational study of French adults, NSAID or aspirin use was a significant risk factor for GERD symptoms [39]. Similar studies from different parts of the globe, including US and UK showed that GERD symptoms were more common in NSAID users than in non-users [40][41][42][43]. However, a recent study from Moscow reported that NSAID use did not affect the prevalence of GERD [44].…”
Section: Discussionmentioning
confidence: 99%
“…In a Spanish study in which factors were related to prevalence, the severity and progress of GERD symptoms were investigated using a reflux questionnaire which was administered to 2,500 people by telephone; it was demonstrated that the intake of 1-5 tablets of ASA per week mildly increased reflux symptoms (p<0.05) and that the severity of reflux symptoms increased with weekly intake of 6-9 tablets (16). In another retrospective multicenter study, while the development of heartburn in patients using ASA was significantly less in comparison to other NSAIDs (OR: 1.44, 95% CI 1.01-2.04), the risk was determined to increase with combined use of ASA and NSAIDs (13).…”
Section: Acetylsalicylic Acidmentioning
confidence: 93%
“…In a case-control study that Ruigó-mez et al (12) conducted with 7159 GERD patients and a control group of 10,000 people, it was documented that the use of NSAIDs increased the development risk of GERD by 1.5 times (OR: 1.5, 95% CI 1.3-1.7) in patients who were currently using NSAIDs and by 1.6 times (OR: 1.6, 95% CI 1.5-1.7) in patients who had used NSAIDs in the past. In another multicenter retrospective study involving 2251 GERD patients that did not involve a control group, the effects of 15-30 days of NSAID use (alone and in combination with ASA) on GERD symptoms was investigated; heartburn developed in 68% of the patients included in the study, and the use of NSAIDs was also observed to result in a statistically significant increase in acute reflux symptoms (p<0.0001) (13).…”
mentioning
confidence: 99%
“…В другом многоцентровом ретроспективном контролируемом исследовании с участием 2251 пациента с ГЭРБ оценено влияние 15-30-дневного применения НПВП (отдельно и в сочетании с АСК) на клинические проявления заболевания. При этом рецидив изжоги регистрировался у 68% пациентов, принимающих НПВП; отмечалось статистически значимое усиление симптомов, характерное для острого рефлюкс-эзофагита (р<0,0001) [11]. Исследование типа «случай-контроль», проведенное в Японии и охватившее 13 млн человек, показало, что все НПВП (как неселективные, так и селективные), низкие дозы АСК, антикоагулянты и антиагреганты повышают риск развития ГЭРБ (р<0,0001).…”
unclassified
“…В другом ретроспективном многоцентровом исследовании показано, что возникновение изжоги у пациентов, принимающих АСК, регистрировалось значительно реже, по сравнению с другими НПВП (ОР 1,44; 95% ДИ 1,01-2,04). При этом риск возникновения изжоги значительно возрастал при совместном использовании АСК и НПВП [11].…”
unclassified